POLITICAL BEHAVIOR AND ELECTORAL VIOLENCE IN NIGERIA: ANALYSIS OF THE 2011 AND 2015 GENERAL ELECTIONS - IBIRONKE B. DOMINION ADIGUN (International Studies Journal)
A prosperous democracy is only possible when a free and fair election is achieved. If resources and potentials of the nation will be properly maximized, it will begin with an election without intimidation or harassment. The voters should be allowed to freely vote for the candidate and political parties of their choice. Searching through history, it has been discovered that there has been no general election in Nigeria since independence in 1960 that has not been characterized by election violence, which has also led to a serious crisis, violence, disputations, and even bloodshed despite the law governing the electoral process in Nigeria. It is therefore pertinent to investigate the reasons why it has been impossible for Nigeria as a nation to achieve a credible election since inception. Therefore, this paper outlines the common challenges of election and why the political actors prefer electoral violence instead of a free and fair election. Using both primary and secondary data, that is, the historical analysis of data, from different scholarly works, this paper found out that it is germane to analyze the reasons why elections in Nigeria can never be credible and possible solutions, with specific focus on the 2011 and 2015 general elections from the comparative analysis perspectives. The credibility of election has always been on paper, but obviously the actions of the people involved is the direct opposite of what the law says. No doubt, there is need for government to place priority on non-inference in electoral matters, the role of judiciary and re-orientation of politicians, also systems and institutions should work in Nigeria like other advanced countries.